Dialog Generasi Muda: Belajar Dari YIPC Dalam Model Mutualisme Knitter - Sitepu, Andreas; Lelono, Martinus Joko (SAPA - Jurnal Kateketik dan Pastoral, 2025)
The role of young people in interfaith religious communities still faces challenges in character building and understanding in the field of dialogue. This situation arises from the impact of boredom, trauma, fear, stigma, and group divisions they experience. On the other hand, the lack of motivation among young people to engage in dialogue affects their participation, which often ends up as mere enjoyment without beneficial transformation. This study will examine an effort to foster an interest in dialogue among young people through YIPC (Young Interfaith Peacemaker Community). They have been involved in religious diversity issues since 2012, encouraging youth engagement in forms of dialogue: scriptural reasoning, interfaith dialogue, and social dialogue in an open, honest, and profound manner. They are also involved in a transformative process that promotes peace for religions, society, and the nation. This effort will be analysed using Paul F. Knitter's mutualism model. The mutualism model will serve as a basis for analysing YIPC’s dialogue efforts and exploring how understanding, collaboration, and transformation can be achieved in dialogue to create cooperation in addressing interfaith issues. This research will use a literature review method. This study provides relevance for understanding the YIPC process and its potential role in fostering an interest in dialogue among young people.